2014
DOI: 10.3390/nu6051899
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Intakes and Sources of Total and Added Sugars in the Canadian Diet

Abstract: National food supply data and dietary surveys are essential to estimate nutrient intakes and monitor trends, yet there are few published studies estimating added sugars consumption. The purpose of this report was to estimate and trend added sugars intakes and their contribution to total energy intake among Canadians by, first, using Canadian Community Health Survey (CCHS) nutrition survey data of intakes of sugars in foods and beverages, and second, using Statistics Canada availability data and adjusting these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
82
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 5 publications
10
82
2
4
Order By: Relevance
“…Furthermore, Australian apparent consumption data (15) suggest that there has been a declining trend in added sugar intake over the past 40 years. This trend was similar to that observed in other developed countries (16)(17)(18)(19) .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, Australian apparent consumption data (15) suggest that there has been a declining trend in added sugar intake over the past 40 years. This trend was similar to that observed in other developed countries (16)(17)(18)(19) .…”
supporting
confidence: 91%
“…This is 5·7 g/d higher than our findings from the 2011-2012 NNPAS, but the percentage energy from added sugar is similar between the two surveys. Studies from other developed countries also report a declining trend in added sugar consumption (16,18,34,35) . For example, using data from the National Health and Nutrition Examination Survey (NHANES) in the USA, Welsh et al (16) observed a 23·4 g/d decrease in added sugar intake between 1999-2000 and 2007-2008 among US residents aged 2 years or above.…”
Section: Discussionmentioning
confidence: 99%
“…23 Heterogeneity was assessed (Cochran Q statistic) and quantified (I 2 statistic). If I 2 was greater than or equal to 50%, we interpreted this as indicating substantial heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the most recently available cycle of the Canadian Community Health Survey (CCHS)-Nutrition in 2004, sugar (naturally occurring and added) comprised on average 20% of the daily calories consumed by Canadians; 4 subsequent analysis has suggested that added sugars account for over half of total sugar intake, with Canadians obtaining an average of 11%-13% of total energy intake from added sugars. 5 Among Canadians aged 19 and older, over 10% of total sugar intake was obtained from free sugars found in fruit juices and fruit drinks (no differentiation is made between these two beverage categories on the CCHS), with an average of over 15% among children aged 9-18. 4 Therefore, lowering Canadians' fruit juice and fruit drink consumption represents a potential target for reducing sugar consumption below acceptable WHO guidelines.…”
mentioning
confidence: 99%